Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.6064/2012/391734
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Venous Thromboembolism: What Is the Risk and How to Prevent It

Abstract: Venous thromboembolism (VTE) that includes deep vein thrombosis and/or pulmonary embolism is a frequent, severe, and potentially lethal disease. After a first episode, VTE has a strong tendency to recur. While VTE is an acute disease, it may have variable outcomes in early and late phases after initial presentation. Furthermore, the incidence of late, clinically important consequences (postthrombotic syndrome and/or chronic thromboembolic pulmonary hypertension) increases in case of recurrent events. The aims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 178 publications
(208 reference statements)
2
22
0
2
Order By: Relevance
“…The relationships of male sex and cancer to an increased risk of VTE recurrence found in our research are widely established in the literature. 16,22,23,[26][27][28] There is no unanimous consensus on the effect of age on the risk of recurrent VTE, and advancing age has been reported to be associated with both increased and decreased recurrence risk in different studies. 12 In our study, we found an inverse relationship between age and the risk of recurrent VTE in an adjusted analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The relationships of male sex and cancer to an increased risk of VTE recurrence found in our research are widely established in the literature. 16,22,23,[26][27][28] There is no unanimous consensus on the effect of age on the risk of recurrent VTE, and advancing age has been reported to be associated with both increased and decreased recurrence risk in different studies. 12 In our study, we found an inverse relationship between age and the risk of recurrent VTE in an adjusted analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The literature comprises a substantial number of studies that have investigated the risk factors, including the TGMs that may play a key role for rVTE (1,4,5,(8)(9)(10)(11)(12)(13). Although presence of TGM as a risk factor for the index VTE event is undisputed, its impact on the rVTE is a highly debated issue (1,4,5,(9)(10)(11)(12)(14)(15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…This corresponds to annualized risks of recurrent VTE of 40.6% for Week 1, 43.2% for Week 2, 32.8% for Week 3, 27.0% for Week 4, and 20.3% for Week 5. For Weeks 6,7,8,9,10,11, and 12, the annualized risks of recurrent VTE were the following, respectively: 16.6%, 13.5%, 10.4%, 13.0%, 12.0%, and 12.0%.…”
Section: Risk Of Vte Recurrencementioning
confidence: 99%
“…VTE events can be triggered by multiple factors and are typically classified as provoked, unprovoked, and cancer-related. Patients with a provoked VTE event, a consequence of risk factors such as surgery and trauma, have been associated with a three-fold smaller risk of VTE recurrence compared to patients with unprovoked VTE; patients with cancer have been associated with a two-to four-fold higher risk of VTE recurrence compared to other patients [6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%